Near-infrared-emitting heteroleptic cationic iridium complexes derived from 2, 3-diphenylbenzo[g]quinoxaline as in vitro theranostic photodynamic therapy agents. Issue 25 (12th June 2017) - Wang, Li; Yin, Huimin; Cui, Peng; Hetu, Marc; Wang, Chengzhe; Monro, Susan; Schaller, Richard D.; Cameron, Colin G.; Liu, Bingqing; Kilina, Svetlana; McFarland, Sherri A.; Sun, Wenfang
Abstract : Cationic iridium complexes are promising near-infrared-emitting in vitro theranostic photodynamic therapy agents. Abstract : Five heteroleptic cationic iridium complexes with a π-expansive cyclometalating 2, 3-diphenylbenzo[ g ]quinoxaline (dpbq) ligand (C^N ligand) and different diimine ligands (N^N ligands) ( i.e. 2, 2′-bipyridine (bpy, 1 ), phenanthroline (phen, 2 ), 2-(2-pyridinyl)quinoline (pqu, 3 ), 2, 2′-bisquinoline (bqu, 4 ), and 2-(quinolin-2-yl)quinoxaline (quqo, 5 )) were synthesized and characterized. The lowest-energy singlet electronic transitions (S1 states) were mainly dpbq ligand-centred 1 ILCT (intraligand charge transfer)/ 1 MLCT (metal to ligand charge transfer) transitions mixed with some 1 π, π* transitions for complexes1–4 with increased contributions from 1 LLCT (ligand to ligand charge transfer) in3 and4 . For complex5, the S1 state was switched to the 1 LLCT/ 1 MLCT transitions. All five complexes displayed weak near-infrared (NIR) phosphorescence, with maximal emission output spanning 700–1400 nm and quantum yields being on the order of 10 −3 . The triplet state absorptions of1–4 all resembled that of the [Ir(dpbq)2 Cl]2 dimer with lifetimes of ca. 400 ns, while the TA spectrum of5 possessed the characteristics of both the quqo ligand and the [Ir(dpbq)2 Cl]2 dimer with a bi-exponential decay of ca. 5 μs and 400 ns. While the photophysics of these complexes differ slightly, their theranostic photodynamic therapy (PDT) effects varied drastically. All of the complexes were biologically active toward melanoma cells. Complexes2 and3 were the most cytotoxic, with 230–340 nM activity and selectivity factors for melanoma cells over normal skin fibroblasts of 34 to 40 fold. Complexes2, 3, and5 became very potent cytotoxins with light activation, with EC50 values as low as 12–18 nM. This potent nanomolar light-triggered activity combined with a lower dark toxicity resulted in5 having a phototherapeutic index (PI) margin of almost 275. The bpy coligand led to the least amount of dark toxicity of1, while phen and pqu produced cytotoxic but selective complexes2 and3 . The quqo coligand produced the most potent complex5 for in vitro PDT, both in terms of photocytotoxicity and PI. All Ir(iii ) complexes exhibited very bright NIR phosphorescence in melanoma cells. The wide range of cytotoxicity and photocytotoxicity effects within a relatively small class of complexes highlights the importance of the identity of the coligand in the biological activity of the π-expansive biscyclometalated Ir(iii ) complexes, and their bright NIR emission in live cells demonstrates their potential as theranostic PDT agents.